Genetic determinants of impaired awareness of hypoglycemia in type 1 diabetes. Issue 9 (September 2017) - Schouwenberg, Bas J.; Coenen, Marieke J.; Paterson, Andrew D.; Tack, Cees J.; Smits, Paul; Kramers, Cornelis; de Galan, Bastiaan E.
Abstract : Objective: It is likely that impaired awareness of hypoglycemia (IAH) and severe hypoglycemia are in part determined by genetic factors. The aim of this study was to investigate candidate genes for associations with IAH and severe hypoglycemia in a cohort of patients with type 1 diabetes. Participants and methods: Consecutive patients with type 1 diabetes were genotyped for single-nucleotide polymorphisms in or near the genes for the β1 and β2 adrenergic receptor ( ADRB1, ADRB2 ), SORCS1, and BNC2, and for the insertion/deletion polymorphism in the ACE gene. IAH and severe hypoglycemia were assessed using a validated questionnaire. Results: Of 486 patients, 32.5% were classified as having IAH. The Arg16Gly polymorphism of ADRB2 was associated with IAH (odds ratio: 1.49, 95% confidence interval: 1.01–2.20, P =0.046) Gly16 (GG) versus carriers of the A allele. In a haplotype analysis, the association was the highest in patients with GG at position 16 and heterozygous at position 27 (odds ratio: 2.19, 95% confidence interval: 1.33–3.61, P =0.03). There were no associations between IAH and other genes, and none of the studied genes was associated with severe hypoglycemia. Conclusion: Genotypes at two variants of ADRB2 are associated with IAH. This association is comparable with the risk of classical risk factors for IAH. Abstract : Supplemental Digital Content is available in the text.